First report of a mecA-positive multidrug-resistant Staphylococcus pseudintermedius isolated from a dog in New Zealand - Bell, A.; Coombs, Geoffrey; Cater, B.; Douglass, C. (New Zealand Veterinary Association, 2016)
Case History: A 14-year-old neutered male Sealyham terrier was referred for assessment of a persistent pyoderma. It had experienced numerous episodes of dermatitis involving pododermatitis, pyoderma and otitis over the previous 6 years. Clinical Findings: Superficial, focally deep and mucocutaneous pyoderma were present, with yellow mucoid exudate on both nares and the lower lips crusted with haemopurulent exudate. Epidermal collarettes were present on the dorsal and lateral trunk. There were peri-anal crusts and mild erythema was present on the concave aspect of both pinnae. Microbiological Findings: Culture and microbiological testing identified Staphylococcus pseudintermedius as the infecting organism. Kirby-Bauer disc susceptibility testing revealed the isolate was resistant to numerous antimicrobials including oxacillin. PCR testing of the isolate identified the presence of the mecA gene which confers resistance to ß-lactam antimicrobials. Pulsed field gel electrophoresis typing suggested the isolate was not related to the methicillin-resistant S. pseudintermedius that had been reported to be associated with canine infections in Western Australia. Diagnosis: Superficial, deep and mucus membrane pyoderma associated with a multi-drug resistant S. pseudintermedius. Clinical Relevance: This is the first recorded case of canine pyoderma involving methicillin-resistant multidrug-resistant S. pseudintermedius in New Zealand. Treatment of such cases is difficult because the number of effective and available antimicrobials is limited. This finding should raise the awareness of the veterinary and medical professions to the presence of such organisms in New Zealand and stimulate a discussion about possible biosecurity barriers, treatment strategies and prevention of zoonotic and nosocomial infections.